Type of entrepreneurial activity and sustainable development goals - Venâncio, Ana (2022)
In this study, we conduct an exploratory study with the aim to investigate whether the type of entrepreneurial activity contributes to the achievement of sustainable development goals (SDGs) in its five dimensions (people, prosperity, planet, peace, and partnership). In addition, we evaluate whether foreign direct investment (FDI) strengthens or reduces these relations. To do so, we apply a multivariate analysis to a sample of 67 countries and find that entrepreneurship contributes negatively to the achievement of SDGs. This eect is mostly due to necessity and non-innovative entrepreneurships, and is evident in the people, prosperity, and partnership dimensions. Nonetheless, FDI helps to diminish this negative eect, as it improves the relation between entrepreneurships, particularly necessity entrepreneurships, and SDG achievement. The main dimension which experiences an improvement due to FDI is people